Dynamics of Job Satisfaction; Analysis of the Influence of Job Placement and Self- Efficacy - Felix Chandra; Nurul Maghfirah (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study examines the relationship between job satisfaction with job placement and self-efficacy variables in the TVRI Ambon environment. By applying quantitative methodology and associative design, the study aims to evaluate the impact of two predictor variables on a single response variable. From a total of 68 employees who are the population, sampling using the Slovin formula resulted in 40 respondents. Data was gathered through the use of a questionnaire, while data processing utilized multiple regression techniques through the SPSS program. The analysis demonstrated that job placement exerted a substantial impact on job satisfaction, while self efficacy did not emerge as a meaningful predictor of employees' contentment with their roles.